Reducing greenhouse gases through green industry: Indonesia's commitment with WHRPG technology in the cement industry sector - Vienna, Winda Carla; Masjud, Yunita Ismail (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: Infrastructure development is a one aspect of measuring the progress of a country. Unfortunately, the process of making cement as one of the main raw materials requires a lot of energy and pr produces exhaust gases which can increase the potential for greenhouse gases. In line with the government's desire to, independently reduce around 29% CO2-equivalent. So with this, the industrial sector is committed to reducing GHG from three emission sources, namely energy, industrial processes and product use as well as industrial waste management. With the Waste Heat Recovery Power Generation (WHRPG) technology, production costs can save IDR 120 billion per year. Where this breakthrough utilizes residual exhaust gas from cement production to save energy use in cement production. It also has the potential to reduce GHG from the remaining production gas. The cement industry generally requires an efficient amount of energy in production, around 50% of production costs come from energy purchases. The objectives of this research are to study the effective and more efficient energy for cement production with WHRPG. Methods: The study method in writing is a literature review. Findings: With Waste Heat Recovery Power Generation (WHRPG) technology, IDR 120 billion per year can save production costs. Where this breakthrough utilizes the remaining exhaust gas from cement production to save energy use in cement production. It also has the potential to reduce GHG from the remaining production gas. Conclusion: Increased costs in energy use and contributors to global warming emissions are the basic foundations in developing energy systems to improve efficiency and reduce emissions. With that, the use of WHRPG is an alternative solution by striving for operational efficiency and reducing exhaust emissions so that it is more environmentally friendly. Where WHRPG utilizes the exhaust gas of cement production.